Measurement and analysis of miniature multilayer patch antenna. - Chair, R. (IEEE Transactions on antennas and propagation)
Although the microstrip patch antenna has a number of advantages such as low-cost and light weight, its physical size is quite large at low microwave frequencies. The designs of multilayer miniature patch antennas with coaxial feed are presented. The first design is a rectangular two-layer patch antenna. Measured results and the results of a preliminary analysis are presented. The projection area of the two-layer patch antenna is kept the same as the single-layer rectangular patch antenna. The resonant frequency of the two-layer antenna is reduced by 50% and has bandwidth of 5%, which is wider than the single-layer rectangular patch antenna. In the second design, the upper patch is cut into a bow-tie shape. This results in a 60% reduction in resonant frequency and a 12% bandwidth. Both the two-layer rectangular and the two-layer bow-tie antennas have good radiation patterns, with cross-polarization level lower than the copolarization level by more than 20 dB